New evidence of predation on humans by cookiecutter sharks in Kauai, Hawaii - Ribéreau-Gayon, Agathe (Int J Legal Med, 2018)
The feeding patterns of species of large sharks on human corpses are well documented in the literature however, that of smaller sharks are less known. This may introduce uncertainty in the medicolegal conclusions. For that reason, accurate identification of patterns of shark predation is very relevant, specifically in areas bordered by the sea. In the case described here, an unidentified lesion was noted on the body of a victim of a scuba diving accident off the island of Kauai, in Hawaii. The aim of this study was to identify the origin of the lesion and investigate its potential to inform on the context of death and/or decomposition. The original outline of the lesion was digitally reconstructed to enable the collection of measurements which were compared with the literature and interpreted with an interdisciplinary approach. This approach permitted to determine that the macroscopic appearance and dimensions of the lesion (major axis = 3.53 cm) were consistent with a bitemark of a cookiecutter shark (Isistius brasiliensis). It was further determined that the bitemark was incomplete and that the specimen involved had a total length of about 24 cm and was likely to be a juvenile. This is the second report in the published literature of cookiecutter bitemarks on humans in the Hawaiian waters. This study brings new evidence-based insights into the interactions between cookiecutter sharks and human remains in marine environments and provides a valuable contribution to the knowledge base on the topic.